Pengembangan Desa Wisata Melalui Pelatihan Pembuatan Kerajinan Tangan Sebagai Souvenir Di Desa Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang - Sartini Sartini; Ida Fauziah; Fastabiqul Khairad; Riyanto (Pelita Masyarakat, 2023)
Denai Lama Village is one of 19 villages in Pantai Labu District, Deli Serdang Regency, which is known as a tourist village with a diversity of biodiversity, including garden ornamental plants that can be used to make handicrafts with economic value. To further develop the potential of yard ornamental plants, through the Medan Area University Community Service Program, the team offered the idea of making oshibana crafts, which is the art of flower arrangement using unused leaves or flowers. Partners in the activity are young women and local PKK mothers. The purpose of the activity is to provide information on the potential of yard ornamental plants to become creative products that have economic value. Implementation of activities with the method of presentation of material and information related to the potential of ornamental plants and the practice of making oshibana directly. It is hoped that this training will increase insight into the utilization of yard ornamental plants into products of economic value. This craft art can be used as decoration for various souvenir products such as bags, frames, key chains and bookmarks.